19th International Conference on Aerospace Sciences and Aviation Technology. Issue 1 (August 2021) - Unknown
Abstract : 6-8 APRIL 2021 CAIRO EGYPT The Military Technical College, Cairo, Egypt has the pleasure to organize the 19th International Conference on Aerospace Sciences & Aviation Technology (ASAT-19), APR 6 - 8, 2021, Cairo, Egypt, sponsored by the Egyptian Ministry of Defense. The conference provides an academic platform for professionals and re-searchers from research, academia and, industrial sectors involved in Aerospace Science and Aviation Technology to exchange knowledge and gain an insight into the state of the art in the latest technology. Conference program includes 11th scientific sessions and 15th invited talks covering the following topics: Aerodynamics and Mechanics of flight Aerospace Combustion and Propulsion Communications and Networks Aerospace structures Aerospace Materials Remote sensing & image processing Renewable Energy Energetic Materials Aerospace Thermophysics Guidance, Navigation and Control Hydraulics and Fluid Power Systems Unmanned Systems Multidisciplinary Design Optimization Wind Energy The (120) full manuscript submitted to the conference secretary, are re-viewed. Just (46) paper have been accepted for suitable publication in the conference. These selected papers will be presented during the conference interval, APR 6 - 8, 2021, in different (11) scientific sessions. In addition to 15 invited talks. Finally, the conference high committee hopes that the conference will achieve its planned mission and would like to acknowledge all contributors, members of the scientific committee and chairmen of the conference session. List of Chairman, Vice Chairman, Conference Rapporteur, Conference Co-Rapporteur, Rapporteur Assistants, Organizing Committee, Scientific Committee are available in this pdf.